Electron collisionless damping of the geodesic acoustic mode in rotating tokamak plasmas. (6th September 2016) - Xie, Baoyi; Guo, Wenfeng; Gong, Xueyu; Yu, Jun; Chen, You; Cao, Jinjia
Abstract: Collisionless damping of the geodesic acoustic mode due to electron dynamics in rotating tokamak plasmas is investigated. A dispersion relation of the geodesic acoustic mode with a non-adiabatic electron response in a rotating tokamak is derived and solved both analytically and numerically. It is found that the collisionless damping of the geodesic acoustic mode, due to electron dynamics, significantly increases with the increasing toroidal rotation, especially in the large safety factor regime. The rotation-induced frequency up-shift of the geodesic acoustic mode increases the resonant velocity, which enables a larger number of electrons to resonate with the geodesic acoustic mode. The significant increase of the number of the resonant electrons significantly enhances the collisionless damping of the geodesic acoustic mode. The result indicates that in rotating tokamak plasmas a more complete picture of the geodesic acoustic mode should include the electron dynamics.